Türkiye’de kanun yapım süreci ve torba kanun uygulamaları - Işık, Cennet Sümeyya (My University, 2016)
TÜRKİYE’DE KANUN YAPIM SÜRECİ VE TORBA KANUN UYGULAMALARI Hukuk; bireylerin, toplumun ve devletin eylemlerini, birbirleriyle olan ilişkilerini konu edinen normatif bir bilimdir. Hukuk üstlendiği bu faaliyetleri çoğu zaman kanunlar yoluyla gerçekleştirir. İçerik ve biçimsel anlamıyla kanun ise, anayasada belirtilen usul ve kurallara uygun olarak, öngörülen yetkili organ tarafından çıkarılan yazılı hukuk kurallarıdır. Kanunların bu tür önemli işlevleri karşılayabilmesi ise nitelikli bir yasama faaliyeti ile mümkün olabilir. Torba kanunlar ülkemizde Avrupa Birliği görüşmeleri kapsamında 2000’li yılların başından itibaren görülmeye başlanmıştır. Torba kanun uygulaması ile tek bir kanun ile birden fazla kanunda değişiklik yapılmaktadır. Geleneksel kanun yapım sürecinden sapma sayılabilecek torba kanun uygulaması Anayasaya, İç tüzüğe ve diğer alt hukuk normlarına aykırıdır. Kanun, Torba Kanun, Kanun Yapım Süreci

CODE MAKING PROCESS AND THE PRACTICE OF OMNIBUS CODE IN TURKEY Law is a normative branch of science which studies actions and interrelations of the individual, the society and the state. Law, most commonly, performs these functions undertaken by means of codes. The code, in its contextual and formal meanings, is a written SUMMARY CODE MAKING PROCESS AND THE PRACTICE OF OMNIBUS CODE IN TURKEY Law is a normative branch of science which studies actions and interrelations of the individual, the society and the state. Law, most commonly, performs these functions undertaken by means of codes. The code, in its contextual and formal meanings, is a written legal norm which is legislated by the constitutionally authorised organ in accordance with the constitutional procedures and principles. Codes require a qualified legislative activity in order to meet these functions. Omnibus codes have appeared in our country by early 2000’s within negotiations with the European Union. Using an omnibüs code, plenty of legal amendments are made through just one single code. The practice of omnibüs code which can be accepted as a deviance from the traditional legislative process does not comply with the Constitution, the parliament’s bylaws and other sub-level legal norms. Code, Omnibus code, Code makıng process
Keywords: Eleştiri ve yorum; Türkiye; Yasa yapma süreci